Characteristics and Treatment of Primary Hepatic Perivascular Epithelioid Cell Tumor (PEComa) in Adults: A Systematic Review - Papantoniou, Konstantinos; Aggeletopoulou, Ioanna; Kalafateli, Maria; Triantos, Christos (Cancers, 2025)
Background: Perivascular epithelioid cell tumors (PEComas) are a rare group of mesenchymal neoplasms with distinctive histological and immunohistochemical features. This systematic review aims to characterize the clinical presentation, diagnostic approach, treatment, and outcomes of adult patients with hepatic PEComa. Methods: We performed a systematic literature search for English-language articles regarding hepatic PEComas using the terms (perivascular epithelioid cell tumor) OR (PEComa) AND (liver) OR (hepatic), up to 25 May 2025. Results: A total of 145 studies encompassing 281 patients were included in the analysis. Most studies originated from Asia. The mean age at diagnosis was 46 years (IQR: 35.25–53.75) with a female predominance. The underlying comorbidities were uncommon among the reported cases, and more than half were asymptomatic at presentation. The tumor presented as a single liver lesion in almost 9 out of 10 patients. Surgical excision was the primary treatment, and diagnosis in 74% of patients was made with positive immunohistochemistry for markers such as HMB-45 and smooth muscle actin. A malignant phenotype was reported in 30 cases. The median follow-up duration was 24 months (IQR: 12–48); recurrence occurred in 17 patients, and disease-related mortality occurred in 8 patients. Conclusions: Primary hepatic PEComa is a rare liver tumor with mostly benign clinical behavior and non-specific presentation. Future studies are needed to support clinician decisions regarding this entity and improve patient care.